Biocompatible lipid nanocarriers for improved skin delivery of fluocinolone acetonide: physicochemical and in vitro performances - Stanković, Tijana; Ilić, Tanja; Dobričić, Vladimir; Tošić, Andjela; Pantelić, Ivana; Savić, Snežana (Archives of Pharmacy, 2023)
In order to improve the delivery of topical corticosteroids into inflammatory skin lesions while reducing the likelihood of adverse effects, lipid nanocarriers have received increasing attention. Hence, this study aimed to develop biocompatible nanoemulsions (NEs) and nanostructured lipid carriers (NLCs) as carriers for fluocinolone acetonide (FA) by carefully optimizing the formulation and process parameters. After an analysis of the relevant physicochemical parameters and stability testing, in vitro release and permeation tests were performed to evaluate whether the nanocarriers affected the penetration of FA into/through the skin compared to a conventional reference product (Sinoderm® cream). The developed NEs exhibited satisfactory physicochemical properties (droplet size
Keywords: fluocinolone acetonide; nanoemulsions; nanostructured lipid carriers; dermal delivery; particle size